The moderating roles of acquired capability for suicide and trait impulsivity in the interpersonal-psychological theory of suicide - Beroin, Angeline Martha P. (Animo Repository, 2017)
The Interpersonal-Psychological Theory of Suicide (IPTS) states that for suicidal behavior to occur, a person must have the desire to die by suicide or suicidal desire and must also have acquired the capability for suicide (ACS). However, the theory did not explain how a personality trait like trait impulsivity which has been associated with suicide, plays a role in its model. This study tested the IPTS wherein ACS and trait impulsivity are moderators for suicidal desire and suicide attempt. Conditional Process Modeling was used to analyze the model with a sample size of 498 participants who are 18 to 29 years old. Results have shown that suicidal desire is a significant predictor of suicide attempt and that ACS and trait impulsivity additively moderate suicidal desire and suicide attempt. ACS was found to positively moderate suicidal desire and suicide attempt, while on the other hand, trait impulsivity negatively moderates the relationship. These results have confirmed the IPTS that both suicidal desire and ACS lead to suicidal behavior and that trait impulsivity can indeed play a role in IPTS. The results and limitations of this study suggest that there is a need to further test the IPTS variables with trait impulsivity using the other models of the Conditional Process Analysis. Furthermore, this study also suggest that the assessment of the individuals capability for suicide must be considered in suicide interventions.